Reflexões de um grupo de professores acerca do melhoramento genético humano a partir de discussões de textos de divulgação científica - Schneider, Eduarda Maria; Meglhioratti, Fernanda Aparecida; Soares, Alexandre Sebastião Ferrari (Faculdade de Educação da Universidade Federal de Minas Gerais, 2017)
ABSTRACT: The possibility of human genetic manipulation raises serious ethical questions. In this context, the objective of this article is to analyze the meanings produced in teachers’ discourses based on the reading and reflection of scientific papers about the theme. The research have used the application of questionnaires and video recording of the speeches of 17 teachers during a course of continuing education. The obtained data were organized and analyzed using French Discourse Analysis. The results pointed out that the discursive and ideological formation of the teachers and their reflections during the course have contributed to their understanding of the different senses produced by the discourses of the present techniques of human genetic manipulation and their ideological approaches with the “old eugenic discourse” and its ethical implications.

RESUMEN: La posibilidad de la manipulación genética humana suscita serios cuestionamientos éticos. En ese contexto, se tiene el objetivo de analizar los sentidos producidos en discursos de profesores a partir de la lectura y la reflexión de textos de divulgación científica acerca del tema. La investigación se realizó por medio de la aplicación de cuestionarios y video grabación de las hablas de 17 profesores durante un curso de formación continuada. Se organizaron y se analizaron los datos constituidos considerándose el Análisis del Discurso Francés. Los resultados indicaron que la formación discursiva e ideológica de los maestros y las reflexiones suscitadas durante el curso contribuyeron a que los docentes comprendieran los distintos sentidos producidos por los discursos de las actuales técnicas de manipulación genética humana y sus aproximaciones ideológicas al “viejo discurso eugenésico” y sus implicaciones éticas.

RESUMO: A possibilidade da manipulação genética humana levanta sérios questionamentos éticos. Nesse contexto objetiva-se analisar os sentidos produzidos em discursos de professores a partir da leitura e reflexão de textos de divulgação científica acerca do tema. A pesquisa foi realizada por meio da aplicação de questionários e vídeo gravação das falas de 17 professores durante um curso de formação continuada. Os dados constituídos foram organizados e analisados mediante Análise de Discurso Francesa. Os resultados apontaram que a formação discursiva e ideológica dos professores e as reflexões suscitadas durante o curso contribuíram para os docentes compreenderem os diferentes sentidos produzidos pelos discursos das atuais técnicas de manipulação genética humana e suas aproximações ideológicas com o “velho discurso eugênico” e suas implicações éticas.
Reflexiones de un grupo de profesores acerca del mejoramiento genético humano a partir de discusiones de textos de divulgación científica
Reflections of a teacher group on human genetic improvement from discussions of scientific divulgation texts
Keywords: Teacher Education; Science Education; Eugenics.; Formação de Professores; Ensino de Ciências; Eugenia.